Behavioral and social issues among volunteers in a preventive HIV vaccine trial in Thailand - Richard A. Jenkins (2018)
Behavioral and social issues were investigated in 363 phase I/II preventive HIV-1 vaccine trial volunteers in Thailand. These issues included risk behavior, HIV knowledge, distress, and social consequences of vaccine trial participation. Data were collected at baseline and at 4-, 8-, and 12-month follow-up visits. Volunteers reported relatively low levels of risk behaviors at baseline and at follow-up. Overtly negative reactions from family or friends were reported by 5.9%. No experiences of discrimination in employment, health care, or insurance were reported. Mean levels of distress were low throughout the trial, and HIV-related knowledge was high, although it was common to consider the possibility of HIV transmission through casual contact. Findings add to the evidence that preventive HIV vaccine trials are feasible in Thailand.